Metrics of story architecture in Asian genre films - Wong, Kenneth Chee Khuen (2014)
This project is a continuation of a previous research, which aims to validate the dominant storytelling theories in films by correlating them with results of quantitative audio-visual analysis of films. While the previous research’s focus is on the stereo soundtrack of films, this project focuses on the 5.1 Surround soundtrack. The project focuses on Asian Vengeance films.